INDEKS MASSA TUBUH RENDAH PADA AWAL KEHAMILAN DAN DEFISIENSI VITAMIN A PADA TRIMESTER KEDUA SEBAGAI FAKTOR RISIKO GANGGUAN PERTUMBUHAN LINIER PADA BAYI LAHIR - Pusparini, Pusparini; Ernawati, Fitrah; Hardinsyah, Hardinsyah; Briawan, Dodik (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The objective of this study was to analyze risk factors related to pregnancy nutritional status on the linear growth of newborn infants. The data used in this research was secondary data from longitudinal studies of nutritional status of pregnant women and their offspring in Bogor District. The variables used included body weight at early pregnancy, body height, weight gain, serum protein, serum albumin, hemoglobin, serum zinc, serum retinol, energy adequacy, protein adequacy and protein density at second and third trimester of pregnancy. A multiple logistic regression was applied to analyze the risk factors. The results showed that vitamin A deficiency (serum retinol <20 μg/dl) of the second trimester and body mass index <18.5 kg/m2 at early pregnancy, are the risk factors of the linear growth of newborn infants (OR = 11.12 and 8.84). This implies that normal nutritional status at early pregnancy is important in preventing stunting among newborn infants.Keywords: body mass index, linear growth, newborn infants, pregnant women, vitamin A deficiency